2013
DOI: 10.1007/s00508-013-0352-0
|View full text |Cite
|
Sign up to set email alerts
|

Bronchogenic cyst of stomach: two cases report and review of the English literature

Abstract: Bronchogenic cysts (BCs) are a rare clinical entity because of anomalism of foregut in the embryonic stage. They have been described mostly within the mediastinum and are uncommon reported arising from the stomach. In this article, we report two cases of BC of stomach identified by pathological examination after surgical resection. It is extremely difficult to make a definitive diagnosis preoperatively just based on imaging findings. Surgical resection may be indicated if malignancy is suspected, or the cyst i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…The present series shows two peak distributions at the ages of b6 years (12/16 pediatric patients) and 20-70 years (22/23 adult patients). Bronchogenic cysts are commonly located in the mediastinum or lung parenchyma, but have also been described in the neck, skin, diaphragm, stomach, abdomen, and retroperitoneum [2][3][4][5][6][7][8][9]12,13]. Mediastinal bronchogenic cysts are observed more often in adults than in children [14,15]; they were found in 21/39 (54%) cases in our series.…”
Section: Discussionmentioning
confidence: 77%
“…The present series shows two peak distributions at the ages of b6 years (12/16 pediatric patients) and 20-70 years (22/23 adult patients). Bronchogenic cysts are commonly located in the mediastinum or lung parenchyma, but have also been described in the neck, skin, diaphragm, stomach, abdomen, and retroperitoneum [2][3][4][5][6][7][8][9]12,13]. Mediastinal bronchogenic cysts are observed more often in adults than in children [14,15]; they were found in 21/39 (54%) cases in our series.…”
Section: Discussionmentioning
confidence: 77%
“…The occurrence of BC in the abdominal cavity may be explained as follows: In the early embryonic stage, the thoracic cavity and the abdominal cavity are connected by a pericardial abdominal cavity tube, and the abdominal cavity is divided into two separate cavities by fusion of the pleura and the peritoneum, which is a component of the diaphragm. In cases developing BC, the abnormal buds of the tracheobronchial tree were cutoff and migrated to the abdomen ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…Differential diagnoses are often extensive and include gastrointestinal stromal tumors, leiomyomas, lymphangiomas, and duplication cysts. Imaging examination shows a simple cystic spherical lesion but is not satisfactory as a definitive diagnostic modality [ 3 , 4 ]. Some authors have reported that endoscopic ultrasound-guided fine needle aspiration cytology showing ciliated respiratory mucosa was helpful for the diagnosis [ 5 ], but preoperative diagnosis generally seems difficult.…”
Section: Case Presentationmentioning
confidence: 99%